Chemical Composition of the Essential Oils of Peucedanum ruthenicum (M. Bieb.) Rochel Leaves and Flowers from Kalardasht: Essential oil of Peucedanum ruthenicum - Alavi, Seyed Hamid Reza; Yassa, Narguss; Fouladi, Fatemeh; Maasumi, Mohammad Ali; Ajani, Yousef; Hadjiakhondi, Abbas (Iranian Journal of Pharmaceutical Sciences, 2006)
The essential oils of leaves and flowers of Peucedanum ruthenicum (M. Bieb.) Rochel (Umbelliferae) were prepared by hydrodistillation separately and analyzed by GC and GC-MS, and the composition of both essential oils were compared together. Sixteen and eleven compounds were identified in leaves and flowers essential oils representing 100% and 96.4% of total oils, respectively. The major components were thymol (57.79%), b-bisabulene (6.10%) for the leaves oil, germacrene-D (45%) and germacrene-B (18.5%) for the flowers oil. The amounts of monoterpenes and sesquiterpenes were not found nearly to be equal in oils of the two parts of the plant.